Economic Evaluation of Household Biogas Unit Production in Supporting Public Policy on Accelerating Renewable Energy Development - Apriliyani, Neng Virly; Fauziah, R. Siti Pupu; Rahmawati, Rita; Sukarelawati, S.; Agustini, A.; Kusumadinata, Ali Alamsyah (Universitas Pendidikan Indonesia (UPI), 2026)
This study explores the economic feasibility and policy relevance of household biogas production as a means to accelerate the transition toward renewable energy and sustainable development. Using an engineering economics approach, the analysis includes cost structures, break-even analysis, return on investment, and capital recovery period. Data were drawn from case studies and market-based estimates of component and operational costs. The findings reveal that despite relatively high operational expenses, production efficiency and consistent market demand ensure long-term economic sustainability. Beyond financial performance, household biogas systems enhance local energy security, reduce environmental degradation, and create community-based employment opportunities. These outcomes provide a strong empirical foundation for evidence-based policymaking, particularly in promoting decentralized energy systems and cross-sector collaboration. The initiative directly supports key Sustainable Development Goals, including clean and affordable energy, inclusive economic growth, and climate action, positioning household biogas as both a profitable and socially impactful renewable energy solution.